Expensive cerebral blood flow measurements alone are useless and misinformative in comatose patients: a comprehensive alternative - Julio Cruz (Arquivos de Neuro-Psiquiatria)
Since the first report addressing quantification of cerebral blood flow (CBF), concomitant assessment of cerebral oxygen consumption was also carried out. Over the years, however, some investigators have emphatically and mistakenly addressed cerebral ischemia in comatose patients, on the basis of CBF measurements alone. In contrast, we have repeatedly reported that ischemia in these patients must be precisely evaluated based on CBF-metabolism coupling or uncoupling, rather than CBF alone. Based on these previous findings, we therefore propose a comprehensive alternative approach, namely the evaluation of brain ischemia in comatose patients based on cerebral metabolic parameters, such as cerebral extraction of oxygen or cerebral lactate release, without expensive CBF measurements.